2018
DOI: 10.1159/000492971
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Endozoochory of <b><i>Cannabis sativa</i></b> Achenes

Abstract: The mechanism by which Cannabis sativa dispersed from its center of origin remains an open question. The literature provides many hypotheses, which we review for the first time, but experiments are few. Darwin was interested in zoochory – the transport of plants by animals. He demonstrated endozoochory (transport of seeds via animal digestive systems) of C. sativa achenes (seeds) by carrier pigeons, but he did not quantify achene survival rates. We assessed mammalian endozoochory in a triplicate experiment: fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Most contemporary research on avian endozoochory is focussed on frugivores, and fruit has been reported to make up 10% or more of the diet of 83 species in the crow family (Corvidae) ( Table 5.1 in Wenny et al, 2016). Dispersal of seeds embedded in the fleshy pulp of an edible berry or fruit has been called "classic endozoochory" (McPartland and Naraine, 2018). This corresponds to the long-standing practice of assigning "dispersal syndromes" to plant species on the basis of diaspore morphology, in which only fleshy-fruited diaspores are assigned to a "endozoochory syndrome" (van der Pijl, 1982;Perez-Harguindeguy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most contemporary research on avian endozoochory is focussed on frugivores, and fruit has been reported to make up 10% or more of the diet of 83 species in the crow family (Corvidae) ( Table 5.1 in Wenny et al, 2016). Dispersal of seeds embedded in the fleshy pulp of an edible berry or fruit has been called "classic endozoochory" (McPartland and Naraine, 2018). This corresponds to the long-standing practice of assigning "dispersal syndromes" to plant species on the basis of diaspore morphology, in which only fleshy-fruited diaspores are assigned to a "endozoochory syndrome" (van der Pijl, 1982;Perez-Harguindeguy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known about the seed dispersal of C. sativa, although it has been hypothesized that gravity, mammals, birds, insects, water and (of course) humans are significant vectors (Small, 2016). For example, the extent of survival through animal digestive systems is undocumented, to the best of my knowledge (McPartland & Naraine, 2018). It would be interesting to examine how survival and dispersal are related to the hull characteristics documented in the present thesis.…”
Section: Future Studies and Limitationsmentioning
confidence: 90%